An Analysis of Senior High School Students Factors to Confidence in Speaking English - Sofiah, Nur; Rahmah, Leny Saili; Hidayat, Hamdan (FKIP - Universitas Riau, 2025)
Despite years of English instruction, many Indonesian senior high school students remain hesitant to speak due to anxiety, fear of mistakes, and low self-efficacy. Speaking confidence is influenced by both internal factors, such as self-perception, motivation, and linguistic competence, and external factors, including teacher support, peer interaction, and classroom environment. This study aims to identify and analyze the internal and external determinants of students’ confidence in speaking English. Using a descriptive qualitative approach, data were collected through open-ended questionnaires distributed to 25 eleventh-grade students at MA Sirnamiskin Bandung. Responses were analyzed thematically to identify recurring themes. Findings reveal that psychological barriers—such as anxiety, low self-esteem, and fear of negative evaluation—significantly hinder students’ confidence. External elements, including supportive teacher feedback, peer encouragement, and school programs like English Day, were found to enhance confidence. Consistent practice through media exposure and real-life interactions also contributed positively. The study concludes that improving speaking confidence requires a holistic approach that addresses emotional, social, and experiential aspects of learning. These results provide practical implications for teachers and school administrators to design supportive and engaging speaking activities that foster students’ confidence in English communication.